EdTech in Senegal: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Senegal; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; pu

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Azfal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence